PODUDARNOST STATUSA UČENIKA I STUDENATA OD 7 DO 21 GODINE SA OČEKIVANIM KONSTRUKTIVNIM PROCESIMA - Dobromir Bonacin (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
The purpose of this work was an identification of actual status of 775 examinees aged 7 - 20 and comparative analysis with expected values according to process model of Bonacin from 2004. There were applied 14 variables from modified Eurofit battery and data were transformed into simple shape with graphical presentation for easier understanding. It was identified a period from the beginning of primary school (I - IV class) with clearly expressed "overshoot" and grammar school with significant total "let down". Through higher primary school classes (V - VIII class) it is possible to re- gister expected status. It was suggested a serious examination of plans and programs as well as other conditions (like teachers work control) for such state overcoming. It is probably necessary to include wire society in serious evaluation, because of, not just se- rious, but complex problem too, with possible long-term consequences.